The Participatory Administration Affecting the Efficiency of School in Koh Samui Management under Suratthani Primary Educational Service Area Office 1: The Participatory Administration Affecting the Efficiency of School in Koh Samui Management under Suratthani Primary Educational Service Area Office 1 - Sommart, Attapon; Pusitrattanavalee, Supattara (RATANABUTH JOURNAL, 2025)
This research aims to study: 1) the level of participatory management in schools in Koh Samui District. 2) the efficiency level of school administration in Koh Samui District. 3) the relationship between participatory management and the efficiency of school administration in Koh Samui District. 4) the predictive variables of participatory management affecting the efficiency of school administration in Koh Samui District under the Office of Surat Thani Primary Educational Service Area 1. quantitative research. The sample group consisted of 287 school administrators and teachers in Koh Samui District under the Office of Surat Thani Primary Educational Service Area 1 in the academic year 2024. Stratified random sampling was used based on school size. The research instrument was a questionnaire. Data were analyzed using percentage, mean, standard deviation, Pearson’s correlation analysis, multiple regression analysis, and stepwise multiple regression analysis. Research Findings 1) The Participatory management in school schools in Koh Samui District was overall at the highest level. 2)The efficiency of school administration in Koh Samui District was at the highest level. 3)The analysis of the relationship between participatory management and school administration efficiency in Koh Samui District found that a positive correlation in all aspects, with a high correlation coefficient (r = 0.651) at a statistical significance level of 0.001. 4)The predictive variables for participatory management affecting school administration efficiency, based on stepwise multiple regression analysis, found that participation in implementation and participation in evaluation jointly predicted school administration efficiency. This forecasting equation could be described as: A. Unstandardized score = 2.159 + .418 (X4) + .131(X3) B. Standardized score y = .527(X4) + .183 (X3).